A miniaturized electrochemical device integrating a biconical microchannel and carbon fiber disk ultramicroelectrode. Issue 16 (14th July 2016) - Chang, Fengxia; Xie, Xia; Li, Meixian; Zhu, Zhiwei
Abstract : A simple, cheap and practicable miniaturized electrochemical device was developed based on a biconical microchannel. Abstract : A simple, cheap and practicable miniaturized electrochemical device based on a biconical microchannel was developed, for which only 1 μL sample solution was needed to implement a typical electrochemical experiment. The practicability of the designed device was validated by detecting uric acid as a model molecule in human serum.